Offline-Capable Mobile Application: A Systematic Literature Review of Research Trends, Synchronization Mechanisms, UI/UX Patterns, and Usability Evaluation - Ningrum, Nenden Citra Softwatul; Nan Cenka, Baginda Anggun; Santoso, Harry Budi (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Limited internet connectivity in developing regions creates a significant digital divide and hinders the adoption of essential digital services in sectors such as health, agriculture, finance, education, and sustainability. This study presents a Systematic Literature Review (SLR) that is sought in the range of 2018-2025, with nine selected studies to synthesize research trends, technical approaches, UI/UX patterns, and evaluation methods on mobile applications that support offline mode. The results of the analysis show that there is an increase in research attention in the 2021–2025 period and show that mobile applications with offline capabilities are relevant in various domains. From a technical point of view, offline support is generally achieved through local storage mechanisms, delayed synchronization, and data integrity controls such as hashing and validation. From a UI/UX perspective, explicit connection status labels, local save confirmations, and sync summaries play an important role in increasing system transparency and maintaining user trust. In addition, recent studies have begun to adopt a broader evaluation approach, including PACMAD-based assessments and scenario-based simulations to test the resilience of systems under conditions of limited or unavailable connectivity. These findings provide practical insights for designers and developers in building mobile applications that are resilient, inclusive, and capable of supporting users in environments with limited network infrastructure.